Plasma power effect to the structure and morphology of strontium stannate thin film - Yusmar Palapa Wijaya; Khairul Anuar Mohamad; Afishah Alias; Zulkifli Azman; Bablu Kumar Ghosh; Abu Bakar Abd Rahman (Semarak Ilmu Publishing, 2024)
Hybrid p-n heterojunction requires a suitable n-type material to support the charge transfer process in photodiode or solar cell applications. Numerous materials have been researched in terms of wet and dry processes. This paper investigated the effect of varied plasma power levels of 50 W, 80 W and 100 W at room temperature on the structure and morphology of an alkaline-earth-based perovskite oxide thin film. Strontium stannate (SrSnO3) thin films are deposited on an indium tin oxide (ITO) substrate using radio frequency (RF) magnetron sputtering at various power levels. The crystallographic orientation of the thin films was examined and it was observed that the (102) plane exhibited dense growth at low power, while the (002) plane showed increased intensity at higher power levels. Additionally, the increase in RF power resulted in larger crystallite and grain sizes, along with modified grain boundaries. Contrarily, surface roughness, resistivity, macrostrain and work adhesion were reduced. The nearly zero W-H linear fitting plot observed at 80 W can serve as a valuable reference for the fabrication of preferred films. These findings provide valuable insights for optimising the growth conditions of alkaline-earth-based perovskite oxide thin films for various applications.